1995
DOI: 10.1111/j.1432-1033.1995.tb20365.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Purification of a Soluble Functional form of the Platelet αIIbβ3 Integrin

Abstract: Platelet glycoproteins aIIb and p3 are membrane proteins that associate to form a Ca'+-dependent heterodimer which constitutes an inducible member of the integrin family at the surface of the cell. To produce a soluble form of this complex, aIIb and p3 were both deleted of their transmembrane and cytoplasmic domains and were expressed in COS cells. Production of the truncated subunits and their mode of assembly were examined by immunoprecipitation experiments and compared to those of wildtype aIIbfl. Synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
12
2
Order By: Relevance
“…15 The underlying molecular mechanism for the thrombasthenic phenotype was the failure of ␤ 3 ⌬616 to complex ␣ IIb . This observation appeared to be in conflict with previous reports in which ␤ 3 -truncated proteins complex ␣ subunits 14,18,19 and the mutated complexes reached the cell surface. 14 Because the apparent discrepancy could be due to differences in the lengths of the deleted fragments, we performed a transient transfection analysis of progressive carboxy-terminal or internally deleted forms of ␤ 3 .…”
Section: Resultscontrasting
confidence: 91%
“…15 The underlying molecular mechanism for the thrombasthenic phenotype was the failure of ␤ 3 ⌬616 to complex ␣ IIb . This observation appeared to be in conflict with previous reports in which ␤ 3 -truncated proteins complex ␣ subunits 14,18,19 and the mutated complexes reached the cell surface. 14 Because the apparent discrepancy could be due to differences in the lengths of the deleted fragments, we performed a transient transfection analysis of progressive carboxy-terminal or internally deleted forms of ␤ 3 .…”
Section: Resultscontrasting
confidence: 91%
“…Moreover, cells transfected with cDNA constructs that excluded the transmembrane and cytoplasmic domains of both GPIIIa and GPIIb still produced GPIIb/IIIa complexes, which were secreted from the cells but were not surface expressed. 16,17 Another study showed that cells transfected with normal GPIIb cDNA and ⌬616-762 GPIIIa cDNA with a predictable exclusion of the transmembrane, the intracellular domains, and a segment of the extracellular domain did not form GPIIb/IIIa complexes. 20 Our data demonstrate that the lack of an even smaller segment of the extracellular domain (⌬657-762) results in the lack of intracellular GPIIb/IIIa complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…GPIIIa from cells containing IJ-1 and Stop657 migrated more rapidly, consistent with the presence of truncated forms of GPIIIa ( Figure 6A). Given that previous studies showed that truncated forms of GPIIb and GPIIIa still formed soluble complexes and that these complexes as well as truncated GPIIIa were secreted by cells, 16,17 we examined the culture medium of IJ-1 and Stop657 cells for GPIIIa. Neither by immunoprecipitation and Western blotting nor by metabolic labeling of the cells and immunoprecipitation with AP5 antibody could we detect any secreted form of GPIIIa in the medium (data not shown).…”
Section: Detection Of Intracellular Gpiiia and Gpiib/iiia Complexes Imentioning
confidence: 99%
“…5 B). Such an immunological cross-reactivity between a 70Ϫ72-kDa soybean plasma membrane component and the β3 subunit has Characterization of AcAt2 a polyclonal antibody raised against A. thaliana glycoproteins purified by RGD peptide already been observed (Schindler et al, 1989) and recently a 58-kDa polypeptide present in total protein extracts of Arabiaffinity. AcAt2, a polyclonal antibody, was raised against Arabidopsis glycocoproteins purified by affinity chromatography on a dopsis shoots and roots has been shown to cross-react with the antibody against chicken β1 polypeptide ( Katembe et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A. thaliana and Rubus protoplasts generated by enzymatic digestion of the cell wall Evidence for the presence of integrin-like proteins relies on the use of exogenous RGD-containing peptides that induce aber-were probed using a 1:100 dilution of rabbit polyclonal antibodies P23 in protoplast buffer (Gamborg's medium containing rant cell wall-plasma membrane interactions and enhanced growth rate of soybean suspension culture (Schindler et al, sucrose 0.06 M and mannitol 0.56 M) or, as a control, rabbit non-immune serum. All samples were then washed with proto-1989), inhibit gravisensing in Characean algae (Wayne et al, 1992) and block the clumping normally seen in protoplasts of plast buffer and incubated with a goat anti-(rabbit IgG)-fluorescein conjugate and viewed with a Nikon Microphot-FXA microsalt-adapted tobacco cells (Zhu et al, 1993), or on immunoblot cross-reactivity with antisera to β3 (Schindler et al, 1989) and scope (Nikon Europe B.V.). The presence of cell wall in the protoplast preparation was examined with the dye Calcofluor, a β1 integrin subunit (Quatrano et al, 1991;Kaminskyj and Heath, 1995;Gens et al, 1996;Katembe et al, 1997).…”
mentioning
confidence: 99%